Effects of bovine colostrum supplementation on serum IGF-I, IgG, hormone, and saliva IgA during training - Mero, A.; Miikkulainen, H.; Riski, J.; Pakkanen, R.; Aalto, J.; Takala, T. (Journal of Applied Physiology, 1997)
The purpose of this study was to examine the effects of bovine colostrum supplementation (Bioenervi) on serum insulin-like growth factor I (IGF-I), immunoglobulin G, hormone, and amino acid and saliva immunoglobulin A concentrations during a strength and speed training period. Nine male sprinters and jumpers underwent three randomized experimental training treatments of 8 days separated by 13 days. The only difference in the treatments was the drink of 125 ml consumed per day. Posttraining increases were noticed for serum IGF-I in the 25-ml Bioenervi treatment (125 ml contained 25 ml Bioenervi) and especially in the 125-ml Bioenervi treatment (125 ml contained 125 ml Bioenervi) compared with the placebo (normal milk whey) treatment (P < 0.05). The change in IGF-I concentration during the 8-day periods correlated positively with the change in insulin concentration during the same periods with 25-ml Bioenervi treatment (r = 0.68; P = 0.045) and with 125-ml Bioenervi treatment (r = 0.69; P = 0.038). Serum immunoglobulin G, hormone, and amino acid and saliva immunoglobulin A responses were similar during the three treatments. It appears that a bovine colostrum supplement (Bioenervi) may increase serum IGF-I concentration in athletes during strength and speed training.